AKUNTABILITAS PENYALURAN BANTUAN LANGSUNG TUNAI TERDAMPAK COVID-19 MELALUI DANA DESA - Kisman Karinda; Ade Putra Ode Amane; Muhammad Lutfi (Program Studi Administrasi Publik, 2022)
This paper aims to determine the Accountability of Direct Cash Aid Disbursement Affected by Covid-19 through Village Funds in Taronggo Village, Bungku Utara District, North Morowali Regency. The research method uses primary data and secondary data. Methods of data collection using the technique of Observation, Questionnaire, Literature Study and Documentation. The technique used is statistical analysis using a statistical formula (percentage) which is used to describe the results of the study. Calculation of the data is given a score based on the type of data collected, namely qualitative data which is then converted into quantitative. After selecting the data, then giving a weighted score for each alternative answer in scoring using the Likert Scale. Then determine the measured variables based on the indicators studied. Based on the results of the distribution of questionnaires to respondents that the Accountability of Direct Cash Assistance Disbursed for the Impact of Covid-19 through Village Funds based on a rating scale is classified as good with a benefit score of 77.55%, accurate 74.29% and eligibility 72.65%.